2021
DOI: 10.1108/ci-10-2019-0109
|View full text |Cite
|
Sign up to set email alerts
|

Offsite construction skills evolution: an Australian case study

Abstract: Purpose The construction industry is currently responding to pressures of industrialisation happening across all sectors. Consequently, offsite construction (OSC) has become a vehicle to achieve industrialisation. This requires changes in traditional construction processes resulting in possible changes in construction skill requirements. Accordingly, the purpose of this study is to identify and review prevailing OSC practices and skills in the Australian construction industry. This study aims to critically ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The study found that these are not identified in the available Australian skill classifications. These, together with some existing skills, need to be part of a new skill classification [36].…”
Section: Global Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that these are not identified in the available Australian skill classifications. These, together with some existing skills, need to be part of a new skill classification [36].…”
Section: Global Perceptionmentioning
confidence: 99%
“…Various relevant skills for better uptake of prefabrication have been identified in extant literature. Ginigaddar et al [36] classified these skills into professional and vocational categories. Professional skills critical for off-site construction are knowledge in DFMA, BIM, digital design, commercial estimating, OSM and logistics production engineering, process efficiency and multi-skills [55][56][57][58].…”
Section: Skills Necessary For High Uptake Of Prefabricationmentioning
confidence: 99%
“…The current state of OSC is primarily affected by industrialization and the increasing shift from onsite construction to factory-based prefabrication [1]. Hence, onsite works are minimal and focus only on assembling buildings or building elements performed by advanced self-directed work package gangs [19]. Depending on the OSC type, the requirement for skilled workers and professionals, both onsite and offsite, varies [53].…”
Section: Addressing Skill Variationsmentioning
confidence: 99%
“…Therefore, this study identifies predominant materials and prominent skills for different OSC types by seeking expert opinions. A detailed predictive analysis of the OSC skills required for different OSC types has been carried out in a parallel study [19].…”
Section: Materials and Skills For Osc Typesmentioning
confidence: 99%
See 1 more Smart Citation